Method for preparing solid electrolyte material with alpha-Li3PS4 phase, and solid electrolyte material

By performing specific heating treatment on the Li ion-conducting sulfide material, a solid electrolyte material with an α-Li3PS4 phase at room temperature was prepared, which solved the problem of difficulty in maintaining the stability of the α-Li3PS4 phase in the prior art, and improved the conductive performance and battery performance of the material.

CN120188233APending Publication Date: 2025-06-20PUBLIC UNIVERSITY CORPORATION OSAKA CITY UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380076470.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-04
Filing Date
2023-11-02
Publication Date
2025-06-20

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the stability of the L-P-S-based sulfide-based solid electrolyte material in the α-Li3PS4 phase at room temperature.

Method used

The solid electrolyte material with an α-Li3PS4 phase is prepared by performing a specific heating treatment on the Li ion-conducting sulfide material, including heating the material to a temperature of 230°C to 350°C, and controlling the temperature increase rate at 200°C to 100°C/min or heating in the range of 200°C to 300°C.

Benefits of technology

The stability of the solid electrolyte material in the α-Li3PS4 phase is achieved at room temperature, and the conductive properties and battery performance of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120188233A_ABST
    Figure CN120188233A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a solid electrolyte material with an alpha-Li3PS4 phase. The problem is solved by a method for producing a solid electrolyte material having an alpha-Li3PS4 phase, the method comprising a step for heating a Li ion-conducting sulfide material, which contains Li, P, and S but does not contain F, Cl, and does not have an alpha-Li3PS4 phase, to a temperature in the range of 230-350 DEG C, the temperature rise rate at 200 DEG C being 100 DEG C / min or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a solid electrolyte material having an α-Li3PS4 phase, and a solid electrolyte material. Background Art

[0002] In recent years, in automobiles such as electric vehicles and hybrid vehicles, and power generation devices such as solar cells and wind power generation, the demand for lithium-ion secondary batteries for storing electric power has increased. In addition, from the viewpoint of ensuring safety, all-solid-state batteries using a solid electrolyte instead of a liquid for the electrolyte layer are being actively studied. Further high performance of these lithium-ion secondary batteries and all-solid-state batteries is required.

[0003] As a solid electrolyte for all-solid-state lithium batteries, sulfide-based solid electrolytes of the L-P-S system have attracted attention due to their high conductivity, and various studies have been conducted. For example, Patent Document 1 discloses an L-P-S-based sulfide-based solid electrolyte obtained by mechanically grinding Li2S, P2S5, and LiBr. In addition, the crystal structures of L-P-S-based sulfide-based solid electrolytes are described in Patent Documents 2 and 3.

[0004] Prior Art Documents

[0005] Patent Documents

[0006] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2017-095351

[0007] Patent Document 2: Japanese Unexamined Patent Application Publication No. 2017-033770

[0008] Patent Document 3: Japanese Unexamined Patent Application Publication No. 2018-174130 Summary of the Invention

[0009] Problems to be Solved by the Invention

[0010] In the crystal structure of sulfide-based solid electrolytes of the L-P-S system, the α-Li3PS4 phase, known as a high-temperature phase, is known to have excellent conductivity, but it is difficult to maintain the α-Li3PS4 phase at room temperature. Therefore, a new method for preparing an L-P-S-based sulfide-based solid electrolyte having an α-Li3PS4 phase even at room temperature is desired.

[0011] Means for Solving the Problems

[0012] The inventors of the present invention have found that by studying the treatment conditions according to the composition of Li-ion conductive sulfide materials, a solid electrolyte material having an α-Li3PS4 phase at room temperature can be provided, thereby completing the present invention.

[0013] Therefore, in the first aspect, according to the present invention, there is provided a method for preparing a solid electrolyte material having an α-Li3PS4 phase, the method comprising: a step of heating a Li-ion conductive sulfide material containing Li, P, and S but not containing F, Cl and not having an α-Li3PS4 phase to a temperature in the range of 230 °C to 350 °C, wherein the heating rate at 200 °C is 100 °C / minute or more.

[0014] In addition, the inventors of the present invention have also found that by studying the composition of the Li-ion conductive sulfide material, it is possible to provide a solid electrolyte material having an α-Li3PS4 phase at room temperature without controlling the heating rate, thus completing the present invention.

[0015] Therefore, in the second aspect, according to the present invention, there is provided a method for preparing a solid electrolyte material having an α-Li3PS4 phase, the method comprising: a step of heating a Li-ion conductive sulfide material containing Li, P, S, F and / or Cl and not having an α-Li3PS4 phase to a temperature in the range of 200 °C to 300 °C.

[0016] According to the present invention, there is provided a solid electrolyte material containing Li, P, S, and F, the composition of which is represented by Li3PS4·aLiF (wherein a satisfies 0 < a ≤ 2.0), and having an α-Li3PS4 phase at room temperature.

[0017] According to the present invention, there is provided a solid electrolyte material having an α-Li3PS4 phase obtained by the above preparation method.

[0018] Effects of the present invention

[0019] According to the present invention, there is provided a method for preparing a solid electrolyte material having an α-Li3PS4 phase. Description of the drawings

[0020] Figure 1 It is a reference diagram of peaks containing an α-Li3PS4 phase in an XRD pattern.

[0021] Figure 2 It is a diagram showing the specific volume and the Li3PS4 phase transition in the rapid heating and rapid cooling crystallization of Li3PS4.

[0022] Figure 3 It is a diagram showing the XRD patterns of the solid electrolyte materials of Examples 1 to 4 and Comparative Example 2.

[0023] Figure 4 It is a diagram showing the XRD patterns of the solid electrolyte materials of Examples 5 to 11 and Comparative Examples 3 and 4.

[0024] Figure 5It is a figure showing the XRD patterns of the solid electrolyte materials of Examples 12 to 18 and Comparative Example 5.

[0025] Figure 6 It is a figure showing the XRD patterns of the solid electrolyte materials of Comparative Examples 1, 6 to 9.

[0026] Figure 7 It is a figure showing the XRD patterns of the solid electrolyte materials of Examples 19, 20 and Comparative Examples 10, 11.

[0027] Figure 8 It is a figure showing the XRD patterns of the solid electrolyte materials of Examples 19, 21 to 24 and Comparative Example 6.

[0028] Figure 9 It is a figure showing the XRD patterns of the solid electrolyte materials of Examples 25 to 28 and Comparative Examples 12, 13.

[0029] Figure 10 It is a figure showing the XRD patterns of the solid electrolyte materials of Examples 29 to 32 and Comparative Examples 14, 15.

[0030] Figure 11 It is a figure showing the XRD patterns of the solid electrolyte materials of Examples 33 to 37 and Comparative Examples 16, 17.

[0031] Figure 12 It is a figure showing the XRD patterns of the solid electrolyte materials of Examples 38 to 42 and Comparative Examples 6, 17.

[0032] Figure 13A It is a figure showing the XPS spectra of F1S after mechanochemical treatment of each composition of the LPS-F system.

[0033] Figure 13B It is a figure showing the XPS spectra of F1S after heat treatment of each composition of the LPS-F system.

[0034] Figure 13C It is a figure showing the XPS spectra of FKL1 after mechanochemical treatment of each composition of the LPS-F system.

[0035] Figure 13D It is a figure showing the XPS spectra of FKL1 after heat treatment of each composition of the LPS-F system.

[0036] Figure 14 It is a figure showing the Arrhenius plots of the solid electrolyte materials of Examples 19, 23 and Comparative Examples 1, 6 to 8.

[0037] Figure 15 It is a figure showing the TG-DTA measurement results of the solid electrolyte materials of Comparative Examples 1, 6, 12, 14 and 16.

[0038] Figure 16 is a graph showing the Raman spectra (100 - 600 cm -1 ) of the solid electrolyte materials of Examples 28, 32, 36, and 41.

[0039] Figure 17 is a graph showing the Raman spectra (100 - 600 cm -1 ) of the solid electrolyte materials of Comparative Examples 6, 12, 14, and 16.

[0040] Figure 18 is a graph showing the composition and heat treatment temperature dependence of the precipitated phases in the Li3PS4 system and the Li3PS4 - LiF system.

[0041] Figure 19 is a reference graph showing the XRD pattern of the crystalline polymorph of Li3PS4.

[0042] Figure 20 is a graph showing the XRD patterns of the solid electrolyte material of Example 40 immediately after preparation and the solid electrolyte material of Example 40 stored at 25°C for 500 hours after preparation. Detailed Description of the Invention

[0043] In this specification, "x - y" (where x and y are specific values) means x or more and y or less (i.e., including both end values) unless otherwise specified.

[0044] (Method for Preparing a Solid Electrolyte Material with an α - Li3PS4 Phase)

[0045] The present invention provides a method for preparing a solid electrolyte material with an α - Li3PS4 phase, the method comprising: a step of heating a Li - ion conductive sulfide material containing Li, P, and S but not containing F, Cl and not having an α - Li3PS4 phase to a temperature in the range of 230°C to 350°C, wherein the heating rate at 200°C is 100°C / minute or more.

[0046] In a specific embodiment, the present invention provides a method for preparing a solid electrolyte material with an α - Li3PS4 phase, the method comprising: a step of heating a Li - ion conductive sulfide material containing Li, P, S, and F and / or Cl and not having an α - Li3PS4 phase to a temperature in the range of 200°C to 300°C.

[0047] In a specific embodiment, the present invention provides a method for preparing a solid electrolyte material having an α-Li3PS4 phase, the method comprising: a step of heating a Li-ion conductive sulfide material containing Li, P, and S but not containing F, Cl and not having an α-Li3PS4 phase to a temperature in the range of 230°C to 350°C, wherein the heating rate at 200°C is 150°C / minute or more.

[0048] In a specific embodiment, the present invention provides a method for preparing a solid electrolyte material having an α-Li3PS4 phase, the method comprising: a step of heating an amorphous Li-ion conductive sulfide material containing Li, P, and S but not containing F, Cl to a temperature in the range of 230°C to 350°C, wherein the heating rate at 200°C is 100°C / minute or more.

[0049] In a specific embodiment, the present invention provides a method for preparing a solid electrolyte material having an α-Li3PS4 phase, the method comprising: a step of heating a Li-ion conductive sulfide material containing Li, P, and S but not containing F, Cl and not having an α-Li3PS4 phase or being in an amorphous state to a temperature in the range of 230°C to 350°C, wherein the heating rate at 200°C is 100°C / minute or more.

[0050] In a specific embodiment, the present invention provides a method for preparing a solid electrolyte material having an α-Li3PS4 phase, the method comprising: a step of heating a Li-ion conductive sulfide material containing Li, P, and S but not containing F, Cl and not having an α-Li3PS4 phase or being in an amorphous state to a temperature in the range of 230°C to 350°C, wherein the heating rate at 200°C is 150°C / minute or more.

[0051] In a specific embodiment, the present invention provides a method for preparing a solid electrolyte material having an α-Li3PS4 phase, the method comprising: a step of heating an amorphous Li-ion conductive sulfide material containing Li, P, S, F, and / or Cl to a temperature in the range of 200°C to 300°C.

[0052] In a specific embodiment, the present invention provides a method for preparing a solid electrolyte material having an α-Li3PS4 phase, the method comprising: a step of heating a Li-ion conductive sulfide material containing Li, P, S, F, and / or Cl and not having an α-Li3PS4 phase or being in an amorphous state to a temperature in the range of 200°C to 300°C.

[0053] In a specific embodiment, the present invention provides a method for preparing a solid electrolyte material having an α-Li3PS4 phase at room temperature, the method comprising: a step of heating a Li-ion conductive sulfide material containing Li, P, and S but not containing F, Cl and not having an α-Li3PS4 phase to a temperature in the range of 230 °C to 350 °C, wherein the heating rate at 200 °C is 100 °C / minute or more.

[0054] In a specific embodiment, the present invention provides a method for preparing a solid electrolyte material having an α-Li3PS4 phase at room temperature, the method comprising: a step of heating a Li-ion conductive sulfide material containing Li, P, and S, and F and / or Cl and not having an α-Li3PS4 phase to a temperature in the range of 200 °C to 300 °C.

[0055] Hereinafter, these preparation methods are also simply referred to as the present preparation method.

[0056] (Li-ion conductive sulfide material)

[0057] The Li-ion conductive sulfide material (hereinafter also simply referred to as the sulfide material) in the present preparation method is not particularly limited as long as it is a material having Li-ion conductivity, containing Li, P, and S but not containing F, Cl and not having an α-Li3PS4 phase, or a material having Li-ion conductivity, containing Li, P, and S, and F and / or Cl and not having an α-Li3PS4 phase. As a material having Li-ion conductivity, containing Li, P, and S but not containing F, Cl and not having an α-Li3PS4 phase, for example, (not having an α-Li3PS4 phase) Li3PS4, Li4P2S6, Li7PS6, Li7P3S 11 , Li 13 P3S 12etc. As materials having Li ion conductivity, containing Li, P, S, and F and / or Cl and not having an α-Li3PS4 phase, for example, Li3PS4·LiF, Li3PS4·0.8LiF, Li3PS4·0.5LiF, Li3PS4·0.2LiF, Li3PS4·0.1LiF, Li3PS4·LiCl, Li3PS4·0.8LiCl, Li3PS4·0.5LiCl, Li3PS4·0.2LiCl, Li3PS4·0.1LiCl, etc. can be cited. The sulfide material not having an α-Li3PS4 phase includes that the sulfide material substantially does not have an α-Li3PS4 phase. For example, when X-ray diffraction (XRD) (using CuKα rays) is performed on a sulfide material at room temperature (in this specification, room temperature means a temperature of 20 to 30 °C), no peak is confirmed between 2θ = 17.5° and 18.5° in the X-ray diffraction pattern, and thus it can be confirmed that it substantially does not have an α-Li3PS4 phase.

[0058] Materials having Li ion conductivity, containing Li, P, S, and F and / or Cl and not having an α-Li3PS4 phase can be represented, for example, by the following formula (I):

[0059] Li3PS4·aLiX (I)

[0060] In the formula, X is F and / or Cl, and a satisfies 0 ≤ a ≤ 2.0. Here, a represents the molar ratio of LiX to Li3PS4. By a being in this range, a sulfide material that can improve battery performance, specifically, a sulfide material having excellent ionic conductivity, can be provided. The range of a is not particularly limited as long as it is within the above range, preferably 0 < a ≤ 2.0, more preferably 0.1 ≤ a ≤ 2.0, more preferably 0.1 ≤ a ≤ 1.5, more preferably 0.1 ≤ a ≤ 1.0. X can be F, can be Cl, or can contain both elements, but preferably contains F, and more preferably is only F. By making X be F, a sulfide material that can further improve battery performance can be provided.

[0061] The content ratio of Li and P contained in the sulfide material is not particularly limited. For example, it is preferably in the range where the molar ratio of Li / P satisfies 1.0 to 10.0 (molar ratio). By making the molar ratio of Li and P be in this range, a sulfide material that can further improve battery performance can be provided. More preferably, it satisfies the range of Li / P = 2.0 to 5.0 (molar ratio), and more preferably satisfies the range of Li / P = 2.9 to 3.1 (molar ratio).

[0062] The sulfide material can be in an amorphous state or not, and is preferably in an amorphous state. When the sulfide material is in an amorphous state, for example, when performing X-ray diffraction (XRD) on the sulfide material (using CuKα rays), in the X-ray diffraction pattern, it can refer to a state where all peaks of 2θ of the XRD have a full width at half maximum (FWHM: unit is degree) of 2.0 or more, or a state where the full width at half maximum is 1.5 or more (FWHM: unit is degree), or a state where the full width at half maximum is 1.0 or more, or a state where the full width at half maximum is 0.5 or more, or a state where peaks cannot be confirmed. Additionally, it can refer to a state where distinct microcrystals cannot be confirmed using a transmission electron microscope. The sulfide material can also be a material obtained by subjecting the material to mechanochemical treatment.

[0063] The sulfide material preferably does not have a β-Li3PS4 phase nor a γ-Li3PS4 phase. Whether the sulfide material has a β-Li3PS4 phase or a γ-Li3PS4 phase can be confirmed as follows: When performing X-ray diffraction (XRD) on the sulfide material at room temperature (using CuKα rays), in the X-ray diffraction pattern, there are two or more independent (i.e., non-overlapping) peaks between 2θ = 17.5° and 18.5°.

[0064] This preparation method can include a step of preparing a sulfide material. The preparation method of the sulfide material is not particularly limited as long as it can physically integrate the raw materials of the sulfide material. As the integration method, for example, a V-type mixer, mechanochemical treatment, a sand mill, and a mixer (homogeneous mixer, planetary mixer, etc.) can be cited. Among them, mechanochemical treatment is preferred. Therefore, in one specific embodiment, this preparation method can include a step of preparing a sulfide material by subjecting the raw materials to mechanochemical treatment.

[0065] As the treatment device for mechanochemical treatment, as long as it is a device that can mix while imparting mechanical energy, it is not particularly limited. For example, a ball mill, a bead mill, a jet mill, a vibration mill, a disk mill, a turbo mill, and mechanical alloying can be used. A ball mill is preferred because it can obtain a large amount of mechanical energy. Among ball mills, a planetary ball mill is preferred because while the pot rotates, the turntable rotates in the opposite direction of the rotation, so that high impact energy can be efficiently generated. The treatment conditions of mechanochemical treatment can be appropriately set according to the treatment device used.

[0066] When the planetary ball mill is used for mechanochemical treatment, the diameter of the balls is not particularly limited, but a range of, for example, 3 to 10 mm can be selected. The rotational speed can be selected from speeds such as 10 to 600 revolutions per minute. There is no particular limitation on the output power either. For example, it can be selected from conditions such as 1 to 100 kWh per 1 kg of raw material. The time for integrated treatment, such as mechanochemical treatment, is not particularly limited and can be set, for example, within the range of 1 to 120 hours.

[0067] As raw materials for a material having Li ion conductivity, containing Li, P, and S but not containing F, Cl, and not having an α-Li3PS4 phase, examples include the simple substances of Li, P, and S or any combination of compounds containing any one or more of Li, P, or S and not containing F, Cl. As specific examples of such a material, for example, Li2S, P2S3, P2S5, Li, P, and S can be cited. Among them, it is preferably at least included Li2S or P2S5, more preferably at least included Li2S and P2S5, and more preferably included Li2S and P2S5 in a molar ratio of Li2S:P2S5 = 3:1.

[0068] As raw materials for a material having Li ion conductivity, containing Li, P, S, and F and / or Cl and not having an α-Li3PS4 phase, examples include the simple substances of Li, P, and S or any combination of compounds containing any one or more of Li, P, S, F, or Cl. As specific examples of such a material, for example, Li2S, P2S3, P2S5, LiF, LiCl, PF3, PF5, PCl3, PCl5, Li, P, and S can be cited. Among them, it is preferably at least included Li2S or P2S5, preferably at least included Li2S and P2S5, and more preferably included Li2S and P2S5 in a molar ratio of Li2S:P2S5 = 3:1.

[0069] The sulfide material during heating can be in the form of powder, particles, film, layer, or granules. The granules can be obtained by pressing the powdery or particulate sulfide material. The layer can be a layer covering other electrode materials such as electrode active materials or their raw materials. The pressing pressure can be selected from pressures within the range of 50 to 2000 MPa. As the coating method, there is no particular limitation. For example, vapor phase methods such as PVD method or CVD method, liquid phase methods such as electroplating or coating method, or solid phase method, coating by applying shear force using a ball mill or the like, or coating by spraying with a sprayer can be used. As the PVD method, vacuum evaporation method, sputtering method, etc. can be cited. As the electrode active material, there is no particular limitation. For example, the positive electrode active material and negative electrode active material described later can be used.

[0070] The heating method is not particularly limited. For example, a heating medium with a temperature above the range of 200°C to 350°C can be cited. By bringing the heating medium maintained at such a temperature into contact with the sulfide material, the sulfide material can be heated to the desired temperature. As the heating medium, for example, heating devices such as electric furnaces, heating plates, heaters, hot presses, muffle furnaces, high-frequency induction heating devices, vacuum heating devices, rotary kilns, sand baths, and salt baths can be used. For example, gases that do not react with the sulfide material, such as argon, can also be used. The heating medium preferably has the function of adjusting temperature and time.

[0071] The heating temperature of a material having Li ion conductivity, containing Li, P, and S but not containing F, Cl, and not having an α-Li3PS4 phase is preferably in the range of 230°C to 2000°C. By setting the heating temperature within this range, a sulfide material that can further improve battery performance can be provided. The heating temperature is preferably in the range of 230°C to 1000°C, more preferably in the range of 230°C to 700°C. The heating temperature here refers to the temperature of the part where the heating medium is in contact with the sulfide material. For example, if the heating medium is a heating device, it refers to the surface temperature of the heating part in contact with the sulfide material. If it is a gas such as argon, it refers to the temperature of the gas in contact with the sulfide material. The heating can be carried out only once or multiple times, but preferably once. In the case of multiple times, the respective heating temperatures are preferably within these temperature ranges.

[0072] The heating temperature of a material having Li ion conductivity, containing Li, P, S, and F and / or Cl and not having an α-Li3PS4 phase is preferably in the range of 200°C to 2000°C. By setting the heating temperature within this range, a sulfide material that can further improve battery performance can be provided. The heating temperature is preferably in the range of 200°C to 1000°C, more preferably in the range of 200°C to 500°C. The heating can be carried out only once or multiple times, but preferably once. In the case of multiple times, the respective heating temperatures are preferably within these temperature ranges.

[0073] In the case of performing multiple heating operations, for example, if two heating operations are performed, a cooling process (described later) may or may not exist between the first heating and the second heating. The second heating can be performed at a temperature higher than that of the first heating or at a lower temperature. For example, when performing three heating operations, if a cooling process exists, it can be performed at two times, between the first heating and the second heating and between the second heating and the third heating, or it can be performed only at either one. In the case of processing a large amount of sulfide material, etc. at one time, it may also include a process of stirring and mixing the sulfide material before heating, during heating, between each heating, and / or after heating. As a mixing method, as long as it is a method that can be used in this field, there is no particular limitation. For example, a V-type mixer, a sand mill, and a mixer (a homogeneous mixer, a planetary mixer, etc.) can be cited.

[0074] The heating time can be appropriately set according to the sulfide material. The heating time is preferably in the range of 1 second to 1200 seconds. By setting the heating time within this range, a sulfide material that can further improve battery performance can be provided. The heating time is preferably in the range of 1 second to 600 seconds, and more preferably in the range of 30 seconds to 360 seconds. In the case of performing multiple heating processes, an appropriate heating time can be set for each heating process.

[0075] In addition, the temperature of the sulfide material in this specification refers to the temperature (measured value) of the surface of the sulfide material. The temperature of the surface of the sulfide material can be measured, for example, by a radiation thermometer using a thermocouple.

[0076] Regarding the heating rate of the sulfide material at the moment when the temperature of the sulfide material reaches, for example, 200 °C, for example, by measuring the temperature of the sulfide material over time to obtain measured values, and taking the measured value at the moment when the temperature reaches 200 °C as a reference (reference point), the value obtained by multiplying the difference between the measured values at the moments x (x is a point that maintains heating, greater than 0 and within 10 seconds) seconds before and after (the measured value at x seconds after the reference point - the measured value at x seconds before the reference point) by 30 / x can be set as the heating rate of the sulfide material at the moment when the temperature of the sulfide material reaches 200 °C. Or, when the sulfide material is heated to 200 °C or higher by a heating device that can apply a certain amount of heat, the heating rate of the sulfide material at the moment when the set temperature (for example, when the sulfide material is heated at a constant rate of 100 °C / minute, it is 100 °C) reaches 200 °C can be considered. In addition, when using a heating medium of 230 °C or higher and there is no reason for the heating rate to decrease, the heating rate at 200 °C can be considered to be substantially 100 °C / minute or higher.

[0077] The heating rate during heating can be appropriately set according to the sulfide material. For example, when the sulfide material has Li ion conductivity, contains Li, P, S, and F and / or Cl and does not have the α-Li3PS4 phase, by setting the heating rate at the moment of reaching 200°C to be 100°C / min or more and heating the sulfide material to a temperature in the range of 200°C to 350°C, a sulfide material having the α-Li3PS4 phase and capable of improving battery performance can be provided. The heating rate of the material having Li ion conductivity, containing Li, P, S, and F and / or Cl and not having the α-Li3PS4 phase is preferably 100°C / min to 3000°C / min, preferably 100°C / min to 1500°C / min, more preferably 100°C / min to 1000°C / min, and even more preferably 150°C / min to 1000°C / min. The heating rate can be not only at the moment of reaching 200°C, but also at a constant heating rate of 100°C / min or more from the start of heating. The range of the heating rate at this time can be appropriately set within the above temperature range.

[0078] To prevent the temperature of the sulfide material from becoming too high, the heating time can be appropriately adjusted in combination with the heating temperature. For example, when the heating temperature is higher than 500°C, by shortening the heating time (e.g., within 60 seconds), it is possible to prevent the temperature of the sulfide material from becoming too high and prevent the formation of crystalline phases other than the α-Li3PS4 phase such as the β-Li3PS4 phase. The formation of a crystalline phase other than the α-Li3PS4 phase can be confirmed by the appearance of two or more independent peaks between 2θ = 17.5° and 18.5° in the X-ray diffraction pattern of X-ray diffraction using CuKα radiation.

[0079] As the combination of the heating temperature and the heating time, it is preferable that the heating time is in the range of 10 seconds to 360 seconds within the heating temperature range of 300°C to 500°C. By setting this combination of the heating temperature and the heating time, a sulfide material capable of further improving battery performance can be provided.

[0080] When the sulfide material is in an amorphous state, it is preferable to heat the temperature of the sulfide material to a temperature exceeding the glass transition temperature of the sulfide material at least once. By heating the sulfide material to a temperature exceeding the glass transition temperature, a sulfide material capable of further improving battery performance can be provided. The glass transition temperature varies depending on the composition of the sulfide material, so the heating temperature is appropriately adjusted according to the composition of the sulfide material. For example, the temperature of the sulfide material can be heated to a temperature 5°C or more higher than the glass transition temperature of the sulfide material, or 10°C or more higher, or 20°C or more higher, or 30°C or more higher, or 50°C or more higher.

[0081] Preferably, the temperature of the sulfide material is heated to above the crystallization temperature of the sulfide material at least once. By heating the sulfide material to a temperature above the crystallization temperature, a sulfide material capable of further improving battery performance can be provided. The crystallization temperature varies depending on the composition of the sulfide material, so the heating temperature is appropriately adjusted according to the composition of the sulfide material. The temperature of the sulfide material can be heated, for example, to a temperature 5°C or more higher than the crystallization temperature of the sulfide material, or to a temperature 30°C or more higher, or to a temperature 50°C or more higher.

[0082] The glass transition temperature and crystallization temperature of the sulfide material can be measured, for example, by thermogravimetric differential thermal analysis (TG-DTA), etc.

[0083] The sulfide material can be maintained at a temperature within the above range for a certain period of time after the above heat treatment. The maintenance time is not particularly limited. For example, it can be in the range of 1 second to 1000 seconds, 1 second to 800 seconds, or 1 to 600 seconds.

[0084] By appropriately adjusting the heating temperature, heating time, heating rate, and the holding time of the temperature, a solid electrolyte material with an α-Li3PS4 phase can be prepared.

[0085] In this preparation method, a step of cooling the heated material may also be included. The cooling method is not particularly limited. It can be cooled by natural cooling, or any cooling device can be used for cooling, but it is preferably cooled using a cooling device. As the cooling device, for example, a liquid rapid solidification device, a rapid cooling sheet preparation device, a solution spinning device, a gas atomization device, a water atomization device, and a rotating disk device, etc. can be used. In addition, a cooling medium that does not react with the sulfide material, such as liquid nitrogen, can also be used.

[0086] The cooling rate during cooling is not particularly limited and can be set appropriately. As the cooling rate, for example, it can be 10°C / minute to 60000°C / minute, or 50°C / minute to 12000°C / minute, or 100°C / minute to 6000°C / minute. Cooling can be carried out at a cooling rate of 50°C / minute or less, or at a cooling rate of 50°C / minute or more. It is preferably cooled at a rate of 100°C / minute or more.

[0087] In a specific embodiment, the present invention provides a method for preparing a solid electrolyte material having an α-Li3PS4 phase, the method comprising: a step of heating a Li-ion conductive sulfide material containing Li, P, and S but not containing F, Cl and not having an α-Li3PS4 phase to a temperature in the range of 230°C to 350°C, wherein the heating rate at 200°C is 100°C / minute or more; and a step of cooling the heated Li-ion conductive sulfide material.

[0088] In a specific embodiment, the present invention provides a method, the method comprising: a step of heating a Li-ion conductive sulfide material containing Li, P, and S and F and / or Cl and not having an α-Li3PS4 phase to a temperature in the range of 200°C to 300°C, and a step of cooling the heated Li-ion conductive sulfide material.

[0089] Each processing step is preferably carried out in an inert atmosphere (such as an argon atmosphere) using a glove box or the like in an environment with a moisture concentration of 10,000 ppm or less and an oxygen concentration of 10,000 ppm or less, and more preferably in an environment with a moisture concentration of 1,000 ppm or less and an oxygen concentration of 1,000 ppm or less.

[0090] Each processing step can also be carried out under a pressure lower than normal pressure or a higher pressure. Normal pressure refers to a range of, for example, 200 hPa before and after 1013 hPa. In addition, the pressure conditions can also be changed, for example, slowly pressurizing, slowly depressurizing, and being at normal pressure during heating and pressurizing during cooling.

[0091] For example, by observing a combination of characteristic peaks of whether the solid electrolyte material has an α-Li3PS4 phase in an X-ray diffraction pattern using CuKα rays by those skilled in the art (for example, the X-ray diffraction pattern of the α-Li3PS4 phase is described in Japanese Patent Laid-Open No. 2017-033770 (Patent Document 2)), it can be determined whether the prepared solid electrolyte material has an α-Li3PS4 phase. Or, in the X-ray diffraction pattern using CuKα rays, between 2θ = 17.5° and 18.5°, only a single peak appears as a peak. Or, in the X-ray diffraction pattern using CuKα rays that has been smoothed and background-processed, when there are two partially overlapping peaks between 2θ = 17.5° and 18.5°, and the peak intensity (bottom peak intensity) of the lowest point between the two peaks (based on the baseline) is 10% or more of the peak intensity (based on the baseline) of any one of the two peaks, it can also be determined that the prepared solid electrolyte material contains an α-Li3PS4 phase (refer to Figure 1)。The intensity of the bottom peak is preferably 40% or more, more preferably 90% or more, of the peak intensity of any one of the two peaks. Smoothing of the X-ray diffraction pattern, background processing, and calculation of the baseline can be performed using commercially available analysis software (for example, SmartLab Studio II manufactured by Rigaku Corporation).

[0092] The prepared solid electrolyte material can have and (α = β = γ = 90°), which are lattice constants calculated by fitting the X-ray diffraction pattern of the solid electrolyte material measured using CuKα radiation at room temperature with a crystal structure analysis software, where the crystal is rectangular and the space group is Pbcn.

[0093] By the method for preparing a solid electrolyte material of the present invention, a solid electrolyte material having an α-Li3PS4 phase (at room temperature) can be obtained. The consideration of the reason why the inventors of the present invention can obtain a solid electrolyte material having an α-Li3PS4 phase (at room temperature) is described herein.

[0094] In the crystal phase of Li3PS4, there are an α-Li3PS4 phase (high-temperature phase), a β-Li3PS4 phase (medium-temperature phase), and a γ-Li3PS4 phase (low-temperature phase). The α-Li3PS4 phase usually appears by heating amorphous Li3PS4 to a high temperature close to 500 °C, and then when the heating is terminated and the temperature is lowered to room temperature, a phase transition from the α-Li3PS4 phase to the γ-Li3PS4 phase occurs. In addition, when Li3PS4 is slowly heated to about 230 °C and maintained at this temperature, the β-Li3PS4 phase precipitates. Here, if the temperature of the heated Li3PS4 is lowered to room temperature, the crystal phase is still maintained in the β-Li3PS4 phase state. Therefore, usually at room temperature, the α-Li3PS4 phase does not exist as a crystal phase. Here, the inventors of the present invention found that by controlling the heating rate to heat (amorphous) Li3PS4, at least when the temperature reaches 200 °C, the heating rate is 100 °C / minute or more, and the α-Li3PS4 phase appears even at a temperature of about 250 °C. In addition, even when returning from this state to room temperature, the α-Li3PS4 phase is maintained and no phase transition to the γ-Li3PS4 phase occurs. Such a situation has been unknown until now.

[0095] Figure 2 Represents the relationship between the heating rate and the temperature reached and the finally formed phase envisioned by the inventors of the present invention. Figure 2 The horizontal axis of represents temperature, and the vertical axis represents the change in specific volume with respect to temperature. Figure 2 In (1) of, it represents a Li-ion conductive sulfide material heated to a temperature above the glass transition point. Figure 2(2)-(4) respectively represent the crystalline phases formed by the heated Li-ion conductive sulfide material. Figure 2 The arrow indicates that a phase transition has occurred.

[0096] When the heating rate at 200 °C is slower than 100 °C / min, through heat treatment, the intermediate-temperature phase β-Li3PS4 phase ( Figure 2 (A)) precipitates. The inventors of the present invention believe that this is because when the heating rate is slow, due to the difference in the temperature dependence of the crystal nucleation rate between the α-Li 3P S4 phase and the β-Li3PS4 phase, compared with the formation of the α-Li3PS4 phase in the supercooled liquid, the nucleation and growth of the β-Li3PS4 phase are faster, and the envelope (embryonic nuclei) of the α-Li3PS4 phase formed in the supercooled liquid dissolves and finally disappears.

[0097] When the heating rate at 200 °C is faster than 100 °C / min, the crystalline phase formed by the Li-ion conductive sulfide material after heating changes due to the temperature reached by heating (the reached temperature). For example, the reached temperature is low (below 230 °C), or no crystalline phase is formed ( Figure 2 (B)), or the β-Li3PS4 phase precipitates ( Figure 2 (C)). The inventors of the present invention believe that this is because the reached temperature is too low to form crystal nuclei, or only the generation and growth of the crystal nuclei of the β-Li3PS4 phase are caused. When the reached temperature is high (above 350 °C), the β-Li3PS4 phase also precipitates ( Figure 2 (C)). The inventors of the present invention believe that this is because when the temperature of the Li-ion conductive sulfide material returns to room temperature after heating is completed, it passes through the temperature range where the phase transition from the α-Li3PS4 phase to the β-Li3PS4 phase may occur, and the phase transition from the α-Li3PS4 phase to the β-Li3PS4 phase occurs. When the reached temperature is in the range of 230 °C to 350 °C, the α-Li3PS4 phase is formed ( Figure 2 (D)). The inventors of the present invention believe that this is because the formation and growth of the α-Li3PS4 phase are faster than the nucleation of the β-Li3PS4 phase in the supercooled liquid, so the α-Li3PS4 phase precipitates, and the Li-ion conductive sulfide material after heating is completed does not pass through the temperature range where the phase transition from the α-Li3PS4 phase to the β-Li3PS4 phase may occur when the temperature returns to room temperature.

[0098] If it is a solid electrolyte material further containing F and Cl in Li3PS4, by heating to a temperature in the range of 200 °C to 300 °C, the α-Li3PS4 phase will appear without controlling the heating rate, and the α-Li3PS4 phase will be maintained even at room temperature. This has also been unknown so far.

[0099] Therefore, through the preparation method of the solid electrolyte material of the present invention, a solid electrolyte material with an α-Li3PS4 phase at room temperature can be obtained. Moreover, for the solid electrolyte material with an α-Li3PS4 phase at room temperature obtained by the preparation method of the solid electrolyte material of the present invention, even after a period of time after preparation, the α-Li3PS4 phase will not be lost, but will be stably maintained. Therefore, through the preparation method of the solid electrolyte material of the present invention, a solid electrolyte material that can maintain the excellent conductivity generated by having an α-Li3PS4 phase for a long time can be obtained.

[0100] (Solid electrolyte material)

[0101] The present invention provides a solid electrolyte material, which contains Li, P, S, and F, and its composition is represented by Li3PS4·aLiF (where a satisfies 0 < a ≤ 2.0), and has an α-Li3PS4 phase at room temperature.

[0102] In addition, the present invention provides a solid electrolyte material, which contains Li, P, S, and F, and its composition is represented by Li3PS4·aLiF (where a satisfies 0 < a ≤ 2.0), and has an α-Li3PS4 phase.

[0103] In a specific embodiment, the present invention also provides a solid electrolyte material, which contains Li, P, S, and F, and its composition is represented by Li3PS4·aLiF (where a satisfies 0 < a ≤ 2.0), and has an α-Li3PS4 phase at room temperature (however, the composition shown in the following formula (II) is excluded).

[0104] Li 4-4β-α-γ P 1+β S 4-γ F γ (II)

[0105] [where 0.2 ≤ α < 1.0, 0 ≤ β ≤ 0.075, 0 < γ ≤ 0.2].

[0106] The range of a of the solid electrolyte material is not particularly limited. By making a in the range of 0 < a ≤ 2.0, a sulfide material that can improve battery performance, specifically, has excellent ionic conductivity, can be provided. The range of a can be 0 < a ≤ 1.5, can also be 0 < a ≤ 1.0, or can also be 0.1 ≤ a ≤ 1.0.

[0107] As Li3PS4·aLiF, for example, Li3PS4·0.01LiF, Li3PS4·0.05LiF, Li3PS4·0.1LiF, Li3PS4·0.2LiF, Li3PS4·0.3LiF, Li3PS4·0.4LiF, Li3PS4·0.5LiF, Li3PS4·0.6LiF, Li3PS4·0.7LiF, Li3PS4·0.8LiF, Li3PS4·0.9LiF, Li3PS4·LiF, Li3PS4·1.5LiF, and Li3PS4·2.0LiF can be cited.

[0108] The reason for having the α-Li3PS4 phase at room temperature is as described above.

[0109] The solid electrolyte material preferably does not show a peak from P2S6 in the Raman spectrum at 370 - 400 cm -1 . The Raman spectrum can be measured, for example, using a laser Raman spectrometer LabRAM HR-800 and using a green laser (532 nm) as the oscillation line. 4- The preparation method of the solid electrolyte material can be carried out, for example, by physically integrating raw materials such as Li2S, P2S5, and LiF. As the integration method, mechanochemical treatment is preferred. The integration method and mechanochemical treatment are as described above.

[0110] The inventors of the present invention believe that in the solid electrolyte material shown by the Li-ion conductive sulfide material containing Li, P, S, and F and / or Cl and not having the α-Li3PS4 phase obtained by a method including a step of heating to a temperature in the range of 200°C to 300°C [for example, the above-mentioned Li3PS4·aLiF (wherein a satisfies 0 < a ≤ 2.0), etc.], F and Cl exist in the solid electrolyte material in the form of LiF and LiCl, respectively, but it is unclear in what state the LiF and LiCl exist in the solid electrolyte material. That is, the Li-ion conductive solid electrolyte material having the α-Li3PS4 phase can be prepared regardless of the heating rate (at room temperature) by heating a Li-ion conductive sulfide material having F and / or Cl, but it is not clear in what state the F and Cl are, and the inventors of the present invention consider it difficult to specifically determine this state.

[0111] (Solid electrolyte composite)

[0112] (Solid electrolyte composite)

[0113] The present invention provides a solid electrolyte composite containing the solid electrolyte material of the present invention.

[0114] In addition to the solid electrolyte material of the present invention, the solid electrolyte composite may also be mixed with solid electrolytes, binders, conductive materials, etc. other than the solid electrolyte material of the present invention.

[0115] The proportion of the solid electrolyte material of the present invention in the solid electrolyte composite can be, for example, 50% by mass or more, 70% by mass or more, and 95% by mass or more.

[0116] The binder is not particularly limited, and binders that can generally be used for battery materials can be used. The binder can be a single binder or a combination of multiple binders.

[0117] The content range of the binder in the solid electrolyte composite can be appropriately selected within the range of 0 to 40% by mass. Among them, it is preferably 30% by mass or less, more preferably 10% by mass or less, and more preferably no binder is included.

[0118] The conductive material is not particularly limited, and conductive materials that can generally be used for battery materials can be used. The conductive material can be a single conductive material or a combination of multiple conductive materials.

[0119] The content range of the conductive material in the solid electrolyte composite can be appropriately selected within the range of 0 to 40% by mass. Among them, it is preferably 30% by mass or less, more preferably 20% by mass or less.

[0120] As the solid electrolyte other than the solid electrolyte material of the present invention included in the solid electrolyte composite, there is no particular limitation, and solid electrolyte materials that can generally be used for battery materials can be used. The solid electrolyte other than the solid electrolyte material of the present invention can be glass or glass-ceramics.

[0121] Glass-ceramics refer to materials having a glass phase and a (precipitated) crystalline phase dispersed in the glass phase. Glass-ceramics can be formed, for example, by heating the glass phase at a temperature above its glass transition point to crystallize (at least a part of) the material. The glass transition point can be measured, for example, by differential thermal analysis (DTA).

[0122] In the case where the solid electrolyte material is glass-ceramics, it can be confirmed, for example, by observing with a transmission electron microscope (TEM) that multiple crystalline phases are included in the glass phase.

[0123] The content range of the solid electrolyte other than the solid electrolyte material of the present invention included in the solid electrolyte composite can be appropriately selected within the range of 0 to 50% by mass. Among them, it is more preferably 40% by mass or less, and further preferably 30% by mass or less.

[0124] The sum of the contents of the binder, conductive material, and solid electrolyte in the solid electrolyte complex is not particularly limited, and is preferably 60% by mass or less, more preferably 50% by mass or less, still more preferably 40% by mass or less, and even more preferably 30% by mass or less.

[0125] The solid electrolyte complex can be formed by mixing the solid electrolyte material of the present invention, a solid electrolyte other than the solid electrolyte material of the present invention, a binder, a conductive material, and the like. The mixing method is not particularly limited as long as it is a method that can be used in this field.

[0126] The solid electrolyte complex and the solid electrolyte material of the present invention can form a solid electrolyte layer, for example, by pressing to a predetermined thickness. The pressing pressure can be selected from pressures in the range of 50 to 2000 MPa.

[0127] (Electrode)

[0128] One embodiment of the present invention provides an electrode containing the solid electrolyte material of the present invention. The electrode can be a positive electrode or a negative electrode. The amount of the solid electrolyte material of the present invention contained in the electrode is not particularly limited, and can be set, for example, in the range of 1 to 50% by mass.

[0129] The electrode may also contain a positive electrode active material, a negative electrode active material, the above-mentioned binder, a conductive material, and a solid electrolyte other than the solid electrolyte material of the present invention that are commonly used in this field.

[0130] The electrode can be obtained, for example, by mixing an electrode active material with an arbitrary binder, a conductive additive, an electrolyte, etc., and pressing the resulting mixture, so as to obtain it in a granular or sheet-like form.

[0131] (Electrode complex)

[0132] The present invention also provides an electrode complex in which the electrode of the present invention and a current collector are combined.

[0133] As the current collector, as long as it can be combined with the electrode of the present invention and perform the function of a current collector, there are no particular limitations on the material, shape, etc. The shape of the current collector can be a shape such as a uniform alloy plate, or a porous shape. In addition, it can also be in the form of a foil, sheet, or film.

[0134] Examples of the raw material of the current collector can include Al, Ni, Ti, Mo, Ru, Pd, stainless steel, steel, etc.

[0135] The electrode complex of the present invention can be an electrode complex formed by combining electrode complexes formed as an electrode and a current collector respectively, or an electrode can be directly formed on the current collector. In the case of direct formation, a known method can be used to coat the electrode active material on the surface of the current collector.

[0136] (All-solid-state secondary battery)

[0137] The present invention provides an all-solid-state secondary battery, which includes the solid electrolyte complex of the present invention and / or the electrode of the present invention. The all-solid-state secondary battery can combine a solid electrolyte layer containing the solid electrolyte complex of the present invention with a positive electrode and a negative electrode commonly used in the art, or can combine a solid electrolyte layer containing the solid electrolyte complex of the present invention with the electrode of the present invention, or can combine a solid electrolyte layer commonly used in the art with the electrode of the present invention.

[0138] The all-solid-state secondary battery can be obtained, for example, by laminating and pressing a positive electrode, a solid electrolyte layer, a negative electrode, and a current collector to obtain a battery cell, and fixing it in a container.

[0139] [Embodiment 1]

[0140] A method for preparing a solid electrolyte material having an α-Li3PS4 phase, the method comprising:

[0141] A heating step of heating a Li-ion conductive sulfide material containing Li, P, and S but not containing F, Cl and not having an α-Li3PS4 phase to a temperature in the range of 230 °C to 350 °C, wherein the heating rate at 200 °C is 100 °C / minute or more.

[0142] [Embodiment 2]

[0143] According to the method described in Embodiment 1, wherein the heating rate at 200 °C in the heating step is 150 °C / minute or more.

[0144] [Embodiment 3]

[0145] According to the method described in Embodiment 1 or 2, wherein the method further includes: a step of obtaining the Li-ion conductive sulfide material by mechanochemical treatment of the raw material of the Li-ion conductive sulfide material.

[0146] [Embodiment 4]

[0147] A method for preparing a solid electrolyte material having an α-Li3PS4 phase, the method comprising:

[0148] A step of heating a lithium-ion conductive sulfide material containing Li, P, S, and F and / or Cl and not having an α-Li3PS4 phase to a temperature in the range of 200°C to 300°C.

[0149] [Embodiment 5]

[0150] According to the method described in Embodiment 4, wherein the solid electrolyte material has a composition represented by the following formula (I):

[0151] Li3PS4·aLiX (I)

[0152] In the formula, X is F and / or Cl, and a satisfies 0 ≤ a ≤ 2.0.

[0153] [Embodiment 6]

[0154] According to the method described in Embodiment 4 or 5, wherein the method further includes: a step of obtaining the lithium-ion conductive sulfide material by mechanochemical treatment of the raw materials of the lithium-ion conductive sulfide material.

[0155] [Embodiment 7]

[0156] A solid electrolyte material containing Li, P, S, and F, wherein its composition is represented by Li3PS4·aLiF, has an α-Li3PS4 phase at room temperature, and in the formula, a satisfies 0 < a ≤ 2.0.

[0157] [Embodiment 8]

[0158] A solid electrolyte material having an α-Li3PS4 phase, which is obtained by the method described in any one of Embodiments 4 to 6.

[0159] Examples

[0160] Hereinafter, the present invention will be described in more detail by way of examples and comparative examples, but the present invention is not limited by any of these examples.

[0161] In the following examples and comparative examples, Li2S is a product of Mitsuwa Chemical Co., Ltd. (purity > 99.9%), LiI, LiBr, LiCl, and P2S5 are products of Sigma Aldrich Co., and LiF is a product of Stella Chemifa Co.

[0162] In addition, in the following examples and comparative examples, a planetary ball mill Pulverisette P-7 manufactured by Fritsch was used. As the X-ray diffraction apparatus, a fully automatic multi-purpose X-ray diffraction apparatus SmartLab manufactured by Rigaku was used. The measurement of ionic conductivity and electronic conductivity was performed using an impedance analyzer (SI-1260) manufactured by Solartron. Raman spectroscopy measurement was performed using a laser Raman spectrometer LabRAM HR-800 manufactured by Horiba, Ltd. As the heating device, a heating plate (PC-420D) manufactured by Cornig was used, and as the thermal analysis device, TG-DTA (Thermo plus EVO2 TG-DTA8121) and DSC (Thermo plus EVO2 DSCvesta) manufactured by Rigaku were used. X-ray photoelectron spectroscopy (XPS) measurement was performed using a K-Alpha X-ray photoelectron spectroscopy system of Thermo Fisher Scientific, and measurement was performed using X-rays of monochromatic Al-Kα (1486.6 eV). The measurement area was approximately 400 μm 2 , and charge neutralization was performed using an Ar + neutralization gun, and etching was performed using Ar ion species.

[0163] As the cooling means, an iron press using liquid nitrogen or a stainless steel plate was used.

[0164] The measurement conditions of the devices used for the evaluation of each specimen in the examples and comparative examples are as follows.

[0165] <X-ray diffraction measurement>

[0166] As the X-ray diffraction apparatus, the above-mentioned SmartLab was used, and through CuKα rays (= 1.54056×10 -10 m), with a tube voltage of 45 kV, a tube current of 200 mA, a scanning angle of 2θ = 10° to 60°, a sampling interval of 0.02°, and a scanning speed of 10° min -1 for structural analysis (hereinafter, all XRD conditions are carried out under this condition).

[0167] <Calculation of ionic conductivity and activation energy>

[0168] AC impedance was measured using the above-mentioned impedance analyzer (SI-1260) by fabricating a polycarbonate cell as described below.

[0169] The current collector uses die steel (SKD), and the insulating material uses polycarbonate with an inner diameter of 10 mm. Weigh 150 mg of each solid electrolyte material and add it to the rod. Use a hydraulic press to perform uniaxial pressing at 360 MPa for 5 minutes to form pellets. Fix the shaft and the rod together by screwing, place them in a glass container, and seal it with a rubber stopper. The measurement frequency is 0.1 Hz to 1×10 6 Hz, the AC amplitude is 10 mV. Take the intersection of the semicircle of the obtained impedance diagram and the real axis as the resistance R of the sample, and calculate the ionic conductivity σ using the following formula.

[0170] σ = (1 / R)·(L / S) (1)

[0171] L: Thickness of the pellet (cm) S: Electrode surface area (0.785 cm 2 )

[0172] The activation energy (E a ) is the slope of the curve of the temperature dependence of the ionic conductivity obtained by plotting the ionic conductivity measured at each temperature and the reciprocal of the absolute temperature. Assuming it follows the Arrhenius law, it is calculated using the following formula.

[0173] σ = Aexp(-E a / RT) (2)

[0174] [σ = Ionic conductivity (Scm -1 ), A: Pre-exponential factor (Scm -1 ), T: Measurement temperature (K), E a : Activation energy (kJmol -1 ), R: Gas constant (kJmol -1 K -1 )]

[0175] <Thermal analysis: TG-DTA>

[0176] In thermogravimetric differential thermal analysis (TG-DTA), use the above-mentioned TG-DTA manufactured by Rigaku Corporation (Thermo plus EVO2 TG-DTA8121). Add about 10 mg of the powder sample to an aluminum sealed pan, and under a nitrogen gas flow (flow rate 100 ml / min), heat it from room temperature to 550 °C at a heating rate of 10 °C / min for measurement.

[0177] In addition, the same device is also used in the heat treatment of the sample after the mechanochemical treatment described below. The heating rate during heat treatment is 100 °C / min.

[0178] <Thermal analysis: DSC>

[0179] Differential scanning calorimetry (DSC) was performed using the Rigaku DSC (Thermo plus EVO2 DSC vesta) described above under a nitrogen gas flow.

[0180] In addition, the same apparatus was also used in the heat treatment of the samples after mechanochemical treatment described below. The heating rate during heat treatment was 150 °C / min.

[0181] <Measurement of Raman spectrum>

[0182] Raman spectrum measurement was performed using the above-mentioned laser Raman spectroscope LabRAM HR-800.

[0183] The powder sample was placed in an Al disk and fixed in argon gas, and measurement was performed using an airtight sample stage (LIBCell-P11D5, nanophoton). Green laser (532 nm) was used as the oscillation line for measurement.

[0184] Hereinafter, a solid electrolyte material (hereinafter also referred to as LPS-based solid electrolyte material) obtained by treating a Li-ion conductive sulfide material containing Li, P, and S but not containing F, Cl and not having an α-Li3PS4 phase under various conditions, and a solid electrolyte material (hereinafter also referred to as LPX-X-based solid electrolyte material) obtained by treating a Li-ion conductive sulfide material containing Li, P, S, and F and / or Cl but not having an α-Li3PS4 phase under various conditions were prepared, and their properties were studied.

[0185] First, the samples of each composition synthesized are described. The synthesis of the halogen-free system (Li2S-P2S5 system) is described first, and then the Li2S-P2S5-LiX system (X is a halogen) containing halogen is described.

[0186] [Regarding LPS-based solid electrolyte materials]

[0187] A total of 5 g of Li2S and P2S5 as raw materials were weighed in a glove box under an argon atmosphere so that the molar ratio of Li2S:P2S5 = 75:25. The weighed raw materials were mixed and subjected to mechanochemical treatment using a planetary ball mill to obtain 75Li2S·25P2S5 amorphous. Hereinafter, the Li2S-P2S5 system without halogen is also referred to as the LPS system.

[0188] Here, the sample obtained by mechanochemical treatment is denoted as the grinding treatment (hereinafter the same in the LPS-X-based solid electrolyte material). This 75Li2S·25P2S5 amorphous is denoted as Li3PS4 (grinding treatment). The raw materials used and the composition (molar ratio) at the time of input are shown in Table 1.

[0189] The conditions for mechanochemical treatment were 70 hours at a rotation speed of 210 rpm. Additionally, a 225 ml pot made of ZrO2 and 450 g of balls with a diameter of 4 mm made of ZrO2 were used.

[0190] The 75Li2S:25P2S5 amorphous material obtained by mechanochemical treatment, i.e., Li3PS4 (grinding treatment), was used as the solid electrolyte sample for Comparative Example 1 below.

[0191] In addition, the environment inside the glove box under an argon atmosphere had a moisture value below -70 °C and an oxygen concentration of 10 ppm or less (all operations performed inside the glove box below were under this condition).

[0192] Table 1

[0193]

[0194] [LPS-X series solid electrolyte materials: Regarding LPS-F series]

[0195] Inside the glove box under an argon atmosphere, a total of 3 g of Li2S, P2S5, and LiF as raw materials were weighed so that the molar ratio was Li2S:P2S5:LiF = 75:25:50. The weighed raw materials were mixed and fed to a planetary ball mill for mechanochemical treatment to obtain Li3PS4·LiF (grinding treatment).

[0196] The conditions for mechanochemical treatment were 20 hours at a rotation speed of 210 rpm. Additionally, a 225 ml pot made of ZrO2 and 450 g of balls with a diameter of 4 mm made of ZrO2 were used.

[0197] The Li3PS4·LiF (grinding treatment) obtained by mechanochemical treatment was used as the solid electrolyte sample for Comparative Example 6 below.

[0198] [LPS-X series solid electrolyte materials: Regarding the LPS-F series solid electrolyte with changed composition]

[0199] In the above Li2S-P2S5-LiF system (hereinafter, sometimes referred to as the LPS-F series), each raw material was weighed in the molar ratios shown in Table 2, and mechanochemical treatment was performed to obtain Li3PS4·0.1LiF (grinding treatment) (Comparative Example 12), Li3PS4·0.2LiF (grinding treatment) (Comparative Example 14), and Li3PS4·0.5LiF (grinding treatment) (Comparative Example 16), respectively.

[0200] The conditions for mechanochemical treatment were carried out in the same manner as in Comparative Example 6 above.

[0201] Table 2

[0202]

[0203] [LPS-X Series Solid Electrolyte Materials: Regarding LPS-Cl Series, LPS-Br Series, and LPS-I Series]

[0204] In addition to the above LPS-F series, mechanochemical treatment was also carried out in the Li2S-P2S5-LiCl series (hereinafter sometimes referred to as the LPS-Cl series), Li2S-P2S5-LiBr series (hereinafter sometimes referred to as the LPS-Br series), and Li2S-P2S5-LiI series (hereinafter sometimes referred to as the LPS-I series) in which the halogen element was changed, and each solid electrolyte sample (grinding treatment) was obtained.

[0205] In a glove box under an argon atmosphere, 1 g in total of Li2S, P2S5, and LiX as raw materials was weighed so that the molar ratio was Li2S:P2S5:LiX = 75:25:50. The weighed raw materials were mixed and supplied to a planetary ball mill for mechanochemical treatment to obtain Li3PS4·LiX (grinding treatment).

[0206] The conditions for mechanochemical treatment were 20 hours at a rotational speed of 510 rpm. In addition, a 45 ml pot made of ZrO2 and 90 g of balls with a diameter of 4 mm made of ZrO2 were used.

[0207] Each solid electrolyte sample obtained by mechanochemical treatment was taken as Li3PS4·LiCl (grinding treatment) (hereinafter, refer to Comparative Example 7), Li3PS4·LiBr (grinding treatment) (hereinafter, refer to Comparative Example 8), Li3PS4·LiI (grinding treatment) (hereinafter, refer to Comparative Example 9) (refer to Table 3 below).

[0208] Table 3

[0209]

[0210] [LPS Series Solid Electrolyte Materials]

[0211] The above Li3PS4 (grinding treatment) was heat-treated at each temperature to obtain an LPS series solid electrolyte material.

[0212] When performing heat treatment, first, the powder of Li3PS4 (grinding treatment) was put into a tablet former with a diameter of 4 mm and pressed and formed at 360 MPa using a hydraulic uniaxial press to produce granules with a thickness of 1 mm or less.

[0213] Place two metal plates made of stainless steel on a heating plate and heat to a specified temperature. The heating of the particles is carried out by placing the produced particles on one metal plate and pressing the particles with the other metal plate. The heating time is 1 minute. After heating for 1 minute, press the particles with a stainless steel plate and rapidly cool them (rapid cooling is carried out by a so-called iron press).

[0214] Here, the specimen obtained by heat treatment is denoted as heated (the same applies to the LPS-X series solid electrolyte materials hereinafter). In addition, the heat treatment temperature can be represented by ht (abbreviation of heat treatment) and a number (3 digits).

[0215] The heating rate takes 1.83 seconds to increase from 188 °C to 211 °C, so it is calculated to be about 750 °C / min at 200 °C. Except for the case where the heating rate is fixed, the following calculations of the heating rate are carried out in the same way.

[0216] <Example 1>

[0217] Adjust the heating temperature (the heating rate at 200 °C is 750 °C / min or more) to make the measured temperature reach 338 °C, and perform heat treatment on Li3PS4 (grinding treatment) (Comparative Example 1) particles to obtain the specimen of Example 1.

[0218] <Examples 2-4, Comparative Example 2>

[0219] As shown in Table 4 (the column of heating rate 750 °C / min or more), change the measured temperature, and perform heat treatment on Li3PS4 (grinding treatment) (Comparative Example 1) particles. Except for changing the heat treatment temperature, it is the same as Example 1.

[0220] <Example 5>

[0221] Adjust the heating temperature to make the measured temperature reach 336 °C, and perform heat treatment on Li3PS4 (grinding treatment) (Comparative Example 1) particles to obtain the specimen of Example 5.

[0222] Specifically, use a DSC device to heat-treat Li3PS4 (grinding treatment) (Comparative Example 1). Set the heating rate of the DSC device to 150 °C / min, end the heating at the moment when the measured temperature of Li3PS4 (grinding treatment) reaches 336 °C, and quickly cool it in liquid nitrogen.

[0223] <Examples 6-11, Comparative Example 3 and Comparative Example 4>

[0224] As shown in Table 4 (the column of heating rate 150 °C / min), change the measured temperature, and perform heat treatment on Li3PS4 (grinding treatment) (Comparative Example 1). Except for changing the heat treatment temperature, it is the same as Example 5.

[0225] <Example 12>

[0226] Adjust the heating temperature to make the measured temperature reach 330 °C, and perform heat treatment on Li3PS4 (ground treatment) (Comparative Example 1) to obtain the sample of Example 12.

[0227] Specifically, use a TG-DTA device to heat-treat Li3PS4 (ground treatment) (Comparative Example 1). Set the heating rate of the TG-DTA device to 100 °C / minute, and end the heating when the measured temperature of Li3PS4 (ground treatment) reaches 330 °C. After heating, use the same TG-DTA device to cool at a cooling rate of up to 50 °C / minute. i3 PS4 (ground treatment) (Comparative Example 1) is heat-treated. Set the heating rate of the TG-DTA device to 100 °C / minute, and end the heating when the measured temperature of Li3PS4 (ground treatment) reaches 330 °C. After heating, use the same TG-DTA device to cool at a cooling rate of up to 50 °C / minute.

[0228] <Examples 13 to 18, Comparative Example 5>

[0229] As shown in Table 4 (the column with a heating rate of 100 °C / minute), change the measured temperature, and perform heat treatment on Li3PS4 (ground treatment) (Comparative Example 1). Except for changing the heat treatment temperature, it is the same as Example 12.

[0230] Table 4

[0231]

[0232] X-ray diffraction (XRD) measurements were performed on the solid electrolyte materials of Examples 1 to 18 and Comparative Examples 2 to 5 described above. The results are as Figures 3 - 5 shown.

[0233] From Figures 3 - 5 the diffraction patterns shown, characteristic peaks appear in the α-Li3PS4 phase around 18°. The splitting of diffraction lines (peaks) can also be seen. This can be understood as that it is not a single β phase, but there is indeed an α phase to the extent that it can appear in the diffraction lines. It can also be said that crystals in which the α phase and the β phase coexist are precipitated, so it is called an α-like phase for convenience here.

[0234] From these results, it can be seen that by setting the heating rates to 750 °C / minute, 150 °C / minute, and 100 °C / minute and performing heat treatment by rapid heating at temperatures up to 350 °C, Li3PS4 with an α phase that is unstable at room temperature can be obtained. In addition, it can be seen that by performing rapid cooling (quenching) using liquid nitrogen or the like while rapidly heating, Li3PS4 with an α phase (α-Li3PS4-like phase) can be obtained.

[0235] [LPS-based and LPS-X-based solid electrolyte materials (X is a halogen)]

[0236] X-ray diffraction measurements were performed on the samples (grinding treatment) that had only been subjected to mechanochemical treatment in the LPS series and LPS-X series (X is a halogen) shown in Table 3, and the results are as Figure 6 shown. As Figure 6 shown, although a part of the raw materials remained, an amorphous halo pattern was observed.

[0237] For the samples of Comparative Examples 6 to 9, heat treatment was carried out at 330 °C. The heat treatment conditions were carried out in the same manner as in Example 1 except for the measured temperature being different. Specifically, particles of Li3PS4·LiF (grinding treatment) (Comparative Example 6), Li3PS4·LiCl (grinding treatment) (Comparative Example 7), Li3PS4·LiBr (grinding treatment) (Comparative Example 8), and Li3PS4·LiI (grinding treatment) (Comparative Example 9) were prepared. The heating temperature of each of these particles was adjusted (the heating rate at 200 °C was 750 °C / minute or more) so that the measured temperature reached 330 °C for heat treatment. As a result, samples of Li3PS4·LiF (ht330) (Example 19), Li3PS4·LiCl (ht330) (Example 20), Li3PS4·LiBr (ht330) (Comparative Example 10), and Li3PS4·LiI (ht330) (Comparative Example 11) were obtained.

[0238] The results of X-ray diffraction measurements of Example 19 and Example 20, Comparative Example 10 and Comparative Example 11 after heat treatment are shown in Figure 7 . As Figure 7 shown, in Example 19 of the LPS-F series containing F (fluorine) as a halogen and Example 20 of the LPS-Cl series containing Cl (chlorine), diffraction lines from the α-phase were observed. On the other hand, in Comparative Example 10 of the LPS-Br series containing Br (bromine) and Comparative Example 11 of the LPS-I series containing I (iodine), diffraction lines from α-Li3PS4 were not observed. In particular, in Comparative Example 10 (LPS-Br series), diffraction lines from the β-phase were observed.

[0239] From this, it can be seen that even among halogens, in the LPS-F series and LPS-Cl series, the α-phase or α-like phase of Li3PS4 crystals precipitates. On the other hand, it can be seen that even for the same halogen element, the α-phase (or α-like phase) does not precipitate in the system containing Br or I. In the LPS-F series and LPS-Cl series, it can be said that F and Cl contribute to the formation of the α-phase, in other words, to the maintenance of the α-phase, which is originally a high-temperature phase, even at room temperature.

[0240] [LPS-F series solid electrolyte material]

[0241] For Li3PS4·LiF (grinding treatment) (Comparative Example 6) obtained by mechanochemical treatment in the composition shown in Table 5 below, heat treatment was carried out at various temperatures to obtain the specimens of Example 19 and Examples 21 to 24. The heat treatment conditions (including the cooling conditions) were the same as those of Example 1 except for the measured temperature. The heat treatment temperatures of Example 19 and Examples 21 to 24 are shown in Table 6 below.

[0242] Table 5

[0243]

[0244] Table 6

[0245]

[0246] The results of X-ray diffraction measurements of Example 19, Examples 21 to 24 and Comparative Example 6 after heat treatment are shown in Figure 8 .

[0247] As Figure 8 shown, in any of Example 19 and Examples 21 to 24, characteristic diffraction lines (asterisks in the figure) were observed in the α phase near 18°. From the peak intensity of the diffraction lines, it can be said that the LPS-F system contributes greatly to the precipitation (formation, stabilization at room temperature) of the α phase compared with the above LPS-Cl system (see Figure 7 ).

[0248] [Regarding LPS-X solid electrolyte materials: Regarding each composition of the LPS-F system]

[0249] Mechanochemical treatment was carried out at the molar ratios shown in Table 2 above. Heat treatment was carried out at various temperatures for the obtained Li3PS4·0.1LiF (grinding treatment) (Comparative Example 12), Li3PS4·0.2LiF (grinding treatment) (Comparative Example 14), Li3PS4·0.5LiF (grinding treatment) (Comparative Example 16) and Li3PS4·LiF (grinding treatment) (Comparative Example 6).

[0250] The measured temperatures of the heat treatment are shown in Table 7. The heat treatment conditions (including the cooling conditions) were the same as those of Example 1 except for the measured temperature.

[0251] Table 7

[0252]

[0253] The results of X-ray diffraction measurements of the specimens of Li3PS4·0.1LiF for Example 25 to 28 and Comparative Example 13 are shown in Figure 9, the results of X-ray diffraction measurements of the Li3PS4·0.2LiF specimens for Examples 29 to 32 and Comparative Examples 14 and 15 are shown in Figure 10 , the results of X-ray diffraction measurements of the Li3PS4·0.5LiF specimens for Examples 33 to 37 and Comparative Examples 16 and 17 are shown in Figure 11 , the results of X-ray diffraction measurements of the specimens for Examples 38 to 42 and Comparative Examples 6 and 17 are shown in Figure 12 . Figures 9 - 12 also shows the results obtained by X-ray diffraction measurements of Li3PS4·0.1LiF (ground treatment) (Comparative Example 12), Li3PS4·0.2LiF (ground treatment) (Comparative Example 14), Li3PS4·0.5LiF (ground treatment) (Comparative Example 16), and Li3PS4·LiF (ground treatment) (Comparative Example 6).

[0254] As Figures 9 - 12 shown, it can be seen that in each specimen of Examples 25 to 42, characteristic diffraction lines were observed in the α-phase near 18°. From this, it can be known that even in Li3PS4·LiF with a large amount of LiF (molar ratio) and Li3PS4·0.1LiF with a small amount of LiF, the α-phase precipitates and this crystalline phase is maintained at room temperature. In contrast, as shown in Comparative Examples 13, 15, and 17, it can be seen that if the temperature is lower than 200 °C, no crystal that can be clearly identified as the α-phase precipitates.

[0255] Figures 13A - 13D shows the XPS spectra of each composition of the LPS-F system. Specifically, Figure 13A and 13C are the XPS spectra of F1S ( Figure 13A ) and FKL1 ( Figure 13C ) in the composition after mechanochemical treatment, Figure 13B and 13D are the XPS spectra of F1S ( Figure 13B ) and FKL1 ( Figure 13D ) in the composition after heat treatment.

[0256] In addition, the spectra shown at the top of each figure are the spectra measured only for LiF and are shown as reference spectra for spectral assignment.

[0257] From Figure 13A to D, it can be seen that in F1S ( Figure 13A or Figure 13B ) and FKL1 ( Figure 13C or Figure 13D ), the spectra of the specimens after heat treatment are different from those of the specimens after mechanochemical treatment (i.e., without heat treatment).

[0258] When looking at the spectrum of F1S, the peak from LiF around 685 eV increases after heat treatment. This is considered to be due to the precipitation of LiF crystals from the amorphous (glass) state. Here, referring to Figure 13A it can be seen that for the specimens with more LiF input from 0.1LiF to LiF, the peak intensity from LiF increases more. Since the existence state of LiF is not clear, it is recorded as LiF for convenience, but it can also be said that there is an upper limit to the dissolution of LiF into the glass.

[0259] On the other hand, when a peak around 684 eV that is not from LiF is also observed, it can be said that there is LiF in the non-crystalline state. However, as described above, the existence state of LiF cannot be clearly defined.

[0260] <Calculation of Ionic Conductivity and Activation Energy>

[0261] Measure the ionic conductivity (σ) of the solid electrolyte specimens of Example 19, Example 23, Comparative Example 1, and Comparative Examples 6 - 8, and calculate the activation energy (E a ).

[0262] Figure 14 Show the Arrhenius plot based on the measured ionic conductivity. Table 8 below shows the ionic conductivity and activation energy measured at room temperature.

[0263] Table 8

[0264] <![CDATA[σ 25 (S cm -1 )]]> <![CDATA[E a (kJ mol -1 )]]> Example 19 <![CDATA[1.3×10 -3 > 32 Example 23 <![CDATA[1.5×10 -3 > 28 Comparative Example 1 <![CDATA[7.5×10 -4 > 35 Comparative Example 6 <![CDATA[1.6×10 -4 > 40 Comparative Example 7 <![CDATA[4.3×10 -4 > 38 Comparative Example 8 <![CDATA[8.2×10 -4 > 35

[0265] From Figure 14 and Table 8, it can be seen that the solid electrolyte materials of Example 19 and 23 with the α-Li3PS4 phase (or a phase similar to the α-Li3PS4 phase) have higher ionic conductivity compared to the solid electrolyte materials of the comparative examples without the α-Li3PS4 phase. In other words, since they show high ionic conductivity, it can be known that the α-phase exists as the main phase.

[0266] <TG-DTA Measurement>

[0267] Perform thermogravimetric measurement (TG-DTA) on the materials of Comparative Example 1, 6, 12, 14, and 16 to obtain the DTA curve.

[0268] The measurement results are shown in Figure 15 . From Figure 15 it can be seen that as the content of LiF increases, the exothermic peak shifts to the low-temperature side. Referring to Figures 9 - 12 it can be seen that it also corresponds to their respective heat treatment temperatures (the precipitation temperature of crystals, the crystallization temperature).

[0269] <Calculation of Ionic Conductivity and Activation Energy>

[0270] For the solid electrolyte materials of Examples 32, 36, and 41 and the solid electrolyte materials of Comparative Examples 6, 14, and 16, the ionic conductivity (κ) was measured to calculate the activation energy (E a ). The measurement method and the like were as described above. The results are shown in Table 9 below.

[0271] Table 9

[0272] <![CDATA[σ 25 (S cm -1 )]]> <![CDATA[E a (kJ mol -1 )]]> Example 32 <![CDATA[1.2×10 -3 > 29 Example 36 <![CDATA[1.1×10 -3 > 32 Example 41 <![CDATA[1.3×10 -3 > 31 Comparative Example 6 <![CDATA[1.4×10 -4 > 39 Comparative Example 14 <![CDATA[3.6×10 -4 > 37 Comparative Example 16 <![CDATA[2.0×10 -4 > 39

[0273] Table 9 shows that the solid electrolyte materials of Examples 32, 36, and 41 having an α-Li3PS4 phase (or a phase similar to the α-Li3PS4 phase) all have a high ionic conductivity of 1.0×10 -3 S cm -1 or higher. From this, it can be seen that regardless of the content (composition) of LiF, by performing heat treatment, a high ionic conductivity considered to be caused by the α-Li3PS4 phase (or a phase similar to the α-Li3PS4 phase) is exhibited.

[0274] This indicates that by preparing a solid electrolyte material having an α-Li3PS4 phase (or a phase similar to the α-Li3PS4 phase) using the preparation method as described above, the α phase that originally exists only at high temperatures can be maintained even at room temperature, and a solid electrolyte with excellent ionic conductivity can be obtained.

[0275] (Measurement of Raman spectrum)

[0276] For the solid electrolyte materials of Examples 28, 32, 36, and 41 and the solid electrolyte materials of Comparative Examples 6, 12, 14, and 16, Raman spectra were measured.

[0277] The measurement results are shown in Figure 16 and Figure 17 . From Figure 16 and 17 , it can be seen that for the sample before heating, the peak of P2S6 4- was confirmed, while the peak of P2S6 4- was not present in the sample after heating. The peak near 420 cm -1 belongs to the PS4 3- unit. From this, it can be seen that Li3PS4 crystals are present in the heat-treated solid electrolyte materials, that is, each sample of the examples.

[0278] <Composition and heat treatment temperature dependence of precipitated phases in Li3PS4-based and Li3PS 4- LiF-based systems>

[0279] Based on the Li3PS4-based and Li3PS4 -The results of X-ray diffraction measurements of each material in the LiF series were evaluated for the compositional and heat-treatment temperature dependence of the presence or absence of the α-Li3PS4 phase (or a phase similar to the α-Li3PS4 phase). Figure 18 The curve is shown. In the figure, • represents a glass-ceramic having an α-Li3PS4 phase or a phase similar to the α-Li3PS4 phase (here, sometimes referred to as the α-phase for convenience), ▲ represents a glass-ceramic having a β-Li3PS4 phase or a phase close to the β-Li3PS4 phase, and ■ represents an amorphous (glass).

[0280] From Figure 18 and Figures 3 - 12 the X-ray diffraction results of various materials shown, it can be seen that an LPS-based solid electrolyte material prepared by heating a Li-ion conductive sulfide material containing Li, P, and S but not containing F, Cl and not having an α-Li3PS4 phase to a temperature in the range of 230°C to 350°C while making the heating rate at 200°C reach 100°C / minute or more has an α-Li3PS4 phase, and an LPS-X-based solid electrolyte material prepared by heating a Li-ion conductive sulfide material containing Li, P, and S and F and / or Cl but not having an α-Li3PS4 phase to a temperature in the range of 200°C to 300°C has an α-Li3PS4 phase. Thus, it can be seen that by setting appropriate heat-treatment conditions for a Li-ion conductive sulfide material containing Li, P, and S (optionally F and / or Cl), a solid electrolyte material having a high ionic conductivity α-Li3PS4 phase that can maintain the original high-temperature phase even at room temperature can be obtained.

[0281] In addition, as described above, compared with a system not containing F (i.e., the LPS system), the system containing F (LPS-F system) can surely precipitate the α-phase even when heat-treated at a low temperature below 300°C, and can maintain the α-phase even at room temperature. Moreover, in the system containing F (LPS-F system), its structure is not clear and it cannot be identified, but since LiF exists in the system, like the LPS system, the α-phase can be precipitated without depending on heat-treatment conditions such as rapid heating.

[0282] (Storage test of solid electrolyte material)

[0283] For the solid electrolyte material of Example 40, the storage stability of the α-Li3PS4 phase was verified. The solid electrolyte material of Example 40 was placed in a container filled with nitrogen and stored at 25°C for 500 hours, and then an experiment was carried out by XRD measurement. The results are shown in Figure 20 . Figure 20 In addition, for comparison, the XRD measurement results of the solid electrolyte material of Example 40 just after preparation are also shown. According to Figure 20, no difference in the X-ray diffraction pattern was found between the sample just after preparation and the sample stored for 500 hours. This indicates that the solid electrolyte material obtained by the preparation method of the present invention can maintain the α-Li3PS4 phase for a long time.

[0284] (Reference: XRD pattern of the crystalline polymorphism of Li3PS4)

[0285] As a reference, the XRD pattern (using CuKα radiation) of the crystalline polymorphism of Li3PS4 is shown in Figure 19 . As Figure 19 shown, α-Li3PS4 shows only a single peak near 2θ = 18° in the X-ray diffraction pattern using CuKα radiation. In contrast, β-Li3PS4 and γ-Li3PS4 have two peaks near 2θ = 18°. From this property, it is possible to determine whether the solid electrolyte material containing Li3PS4 has the α-Li3PS4 phase by observing the peak near 2θ = 18° in the X-ray diffraction pattern using CuKα radiation.

Claims

1. A method for preparing a solid electrolyte material having an α-Li3PS4 phase, the method comprising: A heating step of heating a Li-ion conductive sulfide material containing Li, P, and S but not containing F, Cl and not having an α-Li3PS4 phase to a temperature in the range of 230°C to 350°C, wherein the heating rate at 200°C is 100°C / minute or more.

2. The method according to claim 1, wherein, The heating rate at 200°C in the heating step is 150°C / minute or more.

3. The method according to claim 1 or 2, wherein, The method further includes: A step of obtaining the Li-ion conductive sulfide material by mechanochemical treatment of a raw material of the Li-ion conductive sulfide material.

4. A method for preparing a solid electrolyte material having an α-Li3PS4 phase, the method comprising: A step of heating a Li-ion conductive sulfide material containing Li, P, S, and F and / or Cl and not having an α-Li3PS4 phase to a temperature in the range of 200°C to 300°C.

5. The method according to claim 4, wherein, The solid electrolyte material has the following represented by formula (I) Composition: Li3PS4·aLiX (I), In the formula, X is F and / or Cl, and a satisfies 0 ≤ a ≤ 2.

0.

6. The method according to claim 4 or 5, wherein, The method further includes: A step of obtaining the Li-ion conductive sulfide material by mechanochemical treatment of a raw material of the Li-ion conductive sulfide material.

7. A solid electrolyte material comprising Li, P, S and F, the composition of which is represented by Li3PS4·aLiF and has an α-Li3PS4 phase at room temperature, where a satisfies 0 < a ≤ 2.

0.

8. A solid electrolyte material having an α-Li3PS4 phase, wherein, This material is obtained by the method according to claim 4 or 5.

Citation Information

Patent Citations

  • Α-lithium solid electrolyte

    JP2017033770A

  • Solid electrolyte

    JP2017095351A

  • Solid electrolyte material and method for producing the same

    JP2018174130A